Extensibilidade de ambientes virtuais colaborativos através de estórias interativas não lineares - Duarte, Diego Daniel (Universidade Federal de São Carlos, 2005)
3D Collaborative Virtual Environments (CVE) applications have been impelled mainly by the computer games industry, military and industrial training and product design development. However, most of the existing systems are focused on specific tasks and have a supporting structure, which is closely tight to the application. As a consequence, a change in the application usually means a change in the supporting structure too, making it difficult and expensive to develop new or to extend existing CVEs. This work presents a novel approach to building and extending CVEs through the integration of interactive non-linear stories and Virtual Reality. With this approach, CVEs applications are composed as non-linear stories which can be changed either completely or partly, making it easier for developers to build and/or extend CVEs applications, such as highly dynamic marketing campaigns to 3D virtual shops, customized training courses, educational and entertainment games, etc. To allow the description of the CVE through interactive non-linear stories was developed a description language based on XML, named VEML. The use of a VEML for building a CVE application can facilitate the communication among the different professionals involved in the building of complex VE applications.
Keywords: Realidade virtual; Extensibilidade; VRML (Linguagem de programação); VEML; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO